Artificially designed membranes using phosphonated multiwall carbon nanotube-polybenzimidazole composites for polymer electrolyte fuel cells - Kannan, Ramaiyan; Aher, Pradnya P.; Palaniselvam, Thangavelu; Kurungot, Sreekumar; Kharul, Ulhas K.; Pillai, Vijayamohanan K. (Journal of Physical Chemistry Letters, 2010)
The ability of phosphonated carbon nanotubes to offer an unprecedented approach to tune both proton-conductivity and mechanical stability of hybrid polymer electrolytes based on the polybenzimidazole membrane is demonstrated for fuel cell applications. The covalent attachment between the amino group of the 2-aminoethylphosphonic acid precursor and CNTs has been confirmed by NMR and IR experiments, while EDAX analysis indicates that one out of every 20 carbon atoms is in the CNT is functionalized. Proton conductivity of the composite membrane shows a remarkable 50% improvement in performance while a maximum power density of 780 and 600 mW cm(-2) is obtained for the composite and pristine membranes, respectively. Finally, the ultimate strength determined for the composite and pristine membranes is 100 and 65 MPa, respectively, demonstrating the superiority of the composite. This study opens up a new strategy to systematically tune the properties of polymer electrolytes for special applications by using appropriately functionalized CNTS.